EXPLORING LOCAL COMMUNITY PERCEPTION TO THE ECOTOURISM DEVELOPMENT ATTRACTION AT TUMPA MOUNT FOREST PARK, MANADO, INDONESIA - Jufrina Mandulangi; Benny Irwan Towoliu (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
Tourism development is inseparable from the role of local communities, government, and the private sector. But in practice sometimes only the government and the private sector dominate the development of tourism. Local people who are part and even the owner of a natural and social-cultural tourism attraction are not involved in planning the development of a tourist area and tend to be marginalized. This study aims to explore the perception of local communities towards the development of the Tumpa Mount People's Forest Park as an Ecotourism Attraction. Descriptive qualitative research methods are used to describe or use the details obtained from the respondent’s explanations supported by data that are quantitative. The respondent sampling technique is purposive. The results show that the community supports the establishment of this area is to become eco-tourism attraction.